Melania: early Christianity through the life of one family - Chin, Catherine M.; Schroeder, Caroline T. (Christianity in late antiquity, 2017)
Melania the Elder and her granddaughter Melania the Younger were major figures in early Christian history, using their wealth, status, and forceful personalities to shape the development of nearly every aspect of the religion we now know as Christianity. This volume examines their influence on late antique Christianity and provides an insightful portrait of their legacies in the modern world. Departing from the traditionally patriarchal view, Melania gives a poignant and sometimes surprising account of how the rise of Christian institutions in the Roman Empire shaped our understanding of wome